Towards a New EMU - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2013)
The global financial and economic crisis in 2008-09 followed by a "Euro crisis" - not a crisis of the Euro but a sovereign debt (and/or banking) crisis in some Euro countries - forced to reforms of the asymmetric policy design of the Economic and Monetary Union (EMU). Starting with ad-hoc rescue operations for Greece, Ireland and Portugal a whole bunch of reform steps were necessary to make the Euro area "crisis-proof" for the future. Whether the measures taken are already enough to make the EMU better functioning in future crises is an open question. Nevertheless, the crisis proved to act like Schumpeter's "process of creative destruction": the old (not crisis-proof) institutional set-up has been gradually changed towards a more centralised fiscal policy at EU/Euro area level within a new EMU economic governance. Besides the improvement of the policy instruments of the "Economic Union" of EMU, also the ECB with its monetary policy entered more and more into the role of a lender of last resort of the banking sector. More far-reaching plans (that of Barroso and of Van Rompuy) are already on the table which should transform the European Union from a "Fiscal and Transfer Union" over a "Banking Union" into a genuine EMU with the final goal of a "Political Union", not to mention the "United States of Europe" (USE).
Keywords: 330; Economic and Monetary Union; Eurozone; European Integration; EU; Eurozone; Reform; Europäische Integration; Wirtschaftliche Anpassung; EU-Staaten